Talking about teaching in English: Swedish university lecturers’ experiences of changing teaching language - Airey, John (Ibérica (Castellón de la Plana, Spain), 2011)
This study documents the experiences of Swedish university lecturers when theychange from teaching in their first language to teaching in English. Eighteenlecturers from two Swedish universities took part in a training course for teacherswho need to give content courses in English. As part of the course theparticipants gave mini-lectures in their first language in a subject area that theyusually teach. The following week, the lecturers gave the same lectures again, thistime in English. The pairs of lectures were videoed and commented on by thelecturers themselves and the whole course cohort in an online discussion forum(an input of approximately 60 000 words). In addition, twelve of the lecturerswere interviewed about their experiences of changing language in this way (totalof 4 hours of recorded material). The paper presents a qualitative analysis of thethoughts and experiences expressed by the lecturers in their online discussionsand in the interviews concerning the process of changing the language ofinstruction to English. These results are presented as nine themes. Ninerecommendations for teachers changing to teaching in English are alsopresented. The findings replicate those of earlier studies with one notableexception: the lecturers in this study were acutely aware of their limitations whenteaching in English. It is suggested that this may be due to the lecturers’ relativeinexperience of English-medium instruction.